Cohort study of long-term survival and quality of life following pelvic exenteration. Issue 5 (22nd May 2018) - Steffens, D; Solomon, M J; Young, J M; Koh, C; Venchiarutti, R L; Lee, P; Austin, K
Abstract: Background: Pelvic exenteration (PE) is the preferred treatment available for selected patients diagnosed with locally advanced or recurrent cancer confined to the pelvis. Currently, the majority of the literature reports only on short-term survival and quality-of-life (QoL) outcomes. The aim of this prospective cohort study was to describe long-term survival and QoL outcomes following PE. Methods: This was a cohort study of consecutive patients undergoing PE from 1994 to 2016 at a major teaching hospital in Sydney, Australia. From 2008, consenting patients were also included in a prospective QoL study. Main outcomes were long-term survival and QoL assessed with SF-36 ® and FACT-C questionnaires. Survival was estimated using the Kaplan–Meier method. Results: Some 515 patients underwent PE for locally advanced or recurrent cancer. The cumulative 5- and 10-year overall survival rates were 48·6 and 37·8 per cent respectively. The survival estimates were significantly higher for patients with advanced primary rectal cancer ( P = 0·045) and those in whom a clear resection margin was achieved ( P < 0·001). Some 287 patients were enrolled into the QoL study. Response rates at baseline, 6 months and 5 years were 92·0, 70·0 and 33 per cent respectively. Patients had recovered to their preoperative QoL status by 6 months and, among survivors, QoL remained essentially unchanged during the 5-year follow-up. Conclusion: Patients who underwent PE owing to advanced primary rectal cancer or achieved a clear resection margin had a greater chance of survival. Overall, QoL returned to baseline within 6 months after surgery. Graphical Abstract: Long-term overall survival and quality-of-life outcomes were favourable after pelvic exenteration (PE) surgery. Patients who underwent PE owing to advanced primary rectal cancer or achieved a clear resection margin had greater chances of survival. Although complications are common quality of life returns to baseline in six months